Páginas de um novo tempo: a invenção do corpo infantil e as imagens da infância no boletim da Legião Brasileira de Assistência na Paraíba (1947-1955) - Costa Júnior, José dos Santos (2017)
Between words and gestures, between images and numerical statements (as signs of demographic control), the childhood was historically analyzed in the Paraíba, between the 1940s and 1950s, as a political problem, but in a different way than in other historical moments. Through the state commission of the Brazilian Legion of Assistance (LBA) was designed a whole policy that took the life of children as an object of definition and prescription, being articulated and legitimized by medical, legal and pedagogical knowledge that circulated at the time. This text analyzes the discourses through which the childhood was invented as an object of government and the infant body as the surface of a series of events and knowledges that aimed at caring, educating, sanitizing and disciplining, producing this body historically and culturally. Therefore, I analyze a series of texts and images present in the Bulletin of the LBA, a journal produced by this institution with the objective of giving visibility and repercussion to the policies developed in the state and in the country around childhood and maternity. Articulating it with other printed sources that circulated at the time, I construct the procedures of a genealogy of the practices of government of the childhood. The body is a historical invention and the infant body does not escape this, inasmuch as it has been historically constructed in relations of power and knowledge that fabricated it as the object of a government. Dialoging with Michel Foucault's theoretical-methodological formulations on genealogy and biopolitics and with Giorgio Agamben on bare life and the relations between state, population and life, I try to think about the technologies through which a policy on child life Emerged in Paraíba and Brazil in the period under review, creating the contours so that a power over life - and a certain way of thinking about the future of the child as the future of the nation - was historically possible.